Arctic Seasonal Variability and Extremes, and the Role of Weather Systems in a Changing Climate. Issue 8 (23rd April 2023) - Hartmuth, Katharina; Papritz, Lukas; Boettcher, Maxi; Wernli, Heini
Abstract: The effects of global warming are strongly amplified in the Arctic, causing rapidly rising temperatures and ongoing dramatic loss of sea ice, which itself is subject to large interannual variability. We investigate changes in seasonal‐mean temperature and precipitation, its variability and extremes, using large‐ensemble climate model data with a representative concentration pathway 8.5 forcing scenario for historical (S2000) and end‐of‐century projections (S2100). Our results reveal regionally and seasonally dependent changes in Arctic interannual temperature and precipitation variability that are strongly linked to sea‐ice loss. We show a doubling in precipitation variability over the Arctic Ocean and a significant reduction in temperature variability in the Barents Sea. Extremely warm seasons in S2000 rank among the coldest seasons or become unrealistic in S2100. We further show the key role of large‐scale weather systems for shaping seasonal temperature and precipitation extremes in the Arctic which persists under climate warming. Plain Language Summary: Rapidly rising temperatures and a dramatic reduction of sea ice in recent decades illustrate the impact of climate change in the Arctic. On top of this long‐term trend, Arctic seasonal‐mean conditions can vary substantially from one year to another. In this study, we use a climate model to simulate the Arctic climate at the end of the 21st century following a high‐emission scenario and compare it to simulations representative of the present‐day climate. In general, the Arctic will become warmer and wetter, but large regional and seasonal differences are observed in part owing to local changes of sea‐ice coverage. We find that at very high latitudes, the Arctic will soon experience conditions that are far outside the natural variability in today's climate. Further we show robust patterns of cyclones and anticyclones for seasonal temperature and precipitation extremes in both, present‐day and future Arctic climate. Key Points: Regionally dependent changes in seasonal temperature and precipitation variability are closely linked to local sea‐ice evolution Seasons ranking among the warmest in present‐day climate are soon projected to rank among the coldest or become unrealistic Robust dynamical relationship between weather system frequency and seasonal extremes persists in warming climate